Molecular Dynamics Simulation Study of Stabilizer Association with the Val122Ile Transthyretin Variant - Kevin Morris; John DeSalvo; Iman Deanparvar; Lucus Schneider; Kaleigh Leach; Matthew George; Yayin Fang (Biophysica)
The tetrameric protein transthyretin (TTR) transports the hormone thyroxine in plasma and cerebrospinal fluid. Certain point mutations of TTR, including the Val122Ile mutation investigated here, destabilize the tetramer leading to its dissociation, misfolding, aggregation, and the eventual buildup of amyloid fibrils in the myocardium. Cioffi et al. reported the design and synthesis of a novel TTR kinetic stabilizing ligand, referred to here as TKS14, that inhibited TTR dissociation and amyloid fibril formation. In this study, molecular dynamics simulations were used to investigate the binding of TKS14 and eight TSK14 derivatives to the Val122Ile TTR mutant. For each complex, the ligand’s solvent accessible surface area (SASA), ligand–receptor hydrogen-bonding interactions, and the free energy of ligand-binding to TTR were investigated. The goal of this study was to identify the TSK14 functional groups that contributed to TTR stabilization. TKS14 was found to form a stable, two-point interaction with TTR by hydrogen bonding to Ser-117 residues in the inner receptor binding pocket and interacting through hydrogen bonds and electrostatically with Lys-15 residues near the receptor’s surface. The free energy of TKS14-TTR binding was −18.0 kcal mol−1 and the ligand’s average SASA value decreased by over 80% upon binding to the receptor. The thermodynamic favorability of TTR binding decreased when TKS14 derivatives contained either methyl ester, amide, tetrazole, or N-methyl functional groups that disrupted the above two-point interaction. One derivative in which a tetrazole ring was added to TKS14 was found to form hydrogen bonds with Thr-106, Thr-119, Ser-117, and Lys-15 residues. This derivative had a free energy of TTR binding of −21.4 kcal mol−1. Overall, the molecular dynamics simulations showed that the functional groups within the TKS14 structural template can be tuned to optimize the thermodynamic favorability of ligand binding.